Attitudes towards money and sources of adolescents’ maintenance – initial reports - Gołąb, Sylwia; Będzik, Beata (Postawy wobec pieniędzy a źródła utrzymania adolescentów – doniesienia wstępne, 2020)
Money plays an important economic role in the modern world – they are a medium of exchange, a measure of value, they shape the volume and structure of consumption. On the other hand, they also have psychological significance – they give a sense of security, and affect the self-esteem and motivation of people. The purpose of the study is to assess the attitudes of adolescents towards money in the context of their livelihoods. The analyses are a part of empirical research and concern one of the many aspects of the discussed topic. The study was conducted among 96 students of the Economics Faculty of the West Pomeranian University of Technology in Szczecin, representing people who maintain themselves from various sources. To verify the assumptions, a shortened scale of Attitudes Towards Money by Gąsiorowska was used together with a short questionnaire prepared by the authors regarding sources of income. The obtained research results indicate that there are relationships between some dimensions of attitudes towards money and the source of income
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 8, s. 20-29